Ten questions concerning modeling of distributed multi-energy systems. (November 2019) - Mavromatidis, Georgios; Orehounig, Kristina; Bollinger, L. Andrew; Hohmann, Marc; Marquant, Julien F.; Miglani, Somil; Morvaj, Boran; Murray, Portia; Waibel, Christoph; Wang, Danhong; Carmeliet, Jan
Abstract: Distributed Multi-Energy Systems (D-MES) can sustainably transform the energy supply of buildings, districts, and communities by integrating multiple energy efficient technologies, renewable energy sources, and electricity, gas, and thermal energy networks to provide heating, cooling and electricity services. However, D-MES typically exhibit high levels of technical complexity and encompass various economic, environmental, and policy-related aspects. Consequently, energy models are needed to optimally design and operate D-MES and to analyze their performance in detail. A multitude of aspects must be considered when developing a D-MES model. A first aspect, for instance, is whether an optimization or a simulation approach is more appropriate for the model's scope. Moreover, it is important to accurately represent all the relevant technical characteristics and performance constraints of the various energy generation, storage and distribution network technologies in the model. Additionally, in many cases, adopting approaches from other domains like urban and building energy simulation might be required to identify building requirements for heating, cooling, and electricity. Additional aspects, such as the uncertainty of a model's parameters, which complicates D-MES design and operation decisions, or the computational burdens imposed by extending these models towards the whole-city scale also need to be considered. Finally, methods that can bridge models that focus on specific sub-dimensions of D-MES and allow for more holistic D-MES modeling need to be developed. This paper aims to address these key challenges and to outline recent developments in the field of modeling of D-MES by answering ten questions about the most relevant D-MES modeling dimensions. Highlights: Distributed multi-energy systems (D-MES) encompass various technical, economic, environmental and policy aspects. Modeling is a valuable tool for the design, operation, optimization and performance analysis of D-MES. An overview of the main modeling approaches for D-MES is provided. Specific key aspects of D-MES models and modeling approaches are presented. Uncertainty and cross-domain interactions in D-MES modeling are also discussed.